Small and Medium Size Organization Tax Planning Practice in Baglung, Nepal - Kandel, Ram Raja (The Gaze: Journal of Tourism and Hospitality, 2024)
Tax planning remains a pivotal yet contentious issue, balancing government interests in revenue generation with organizational goals of minimizing tax liabilities. This study adopts a positivist research philosophy, complemented by elements of critical realism, to explore the relationships between strategic, project, and action planning and their impact on tax planning behaviors. Data were collected through structured surveys, which included targeted closed-ended questions to provide a thorough understanding of the phenomenon. This approach ensured clarity and precision in capturing respondents' insights, allowing for a detailed analysis of the underlying trends and patterns. Quantitative analyses, including Chi-square tests, t-tests, two-way ANOVA, and logistic regression, revealed significant impacts of strategic, project, and action planning on tax planning and the mediating role of knowledge and attitudes in these relationships. Additionally, the findings highlight the influence of planning factors on knowledge and attitudes, which subsequently affect tax planning behaviors. The study underscores the importance of integrating strategic, project, and action planning into organizational tax strategies to enhance compliance and efficiency. Future research is encouraged to explore further the integration of behavioral economics, emerging technologies, cross-cultural perspectives, and policy frameworks to enrich the tax planning field.